ILRI In-House reconstituted SARS-CoV-2 RT-qPCR testing kit as an alternative to the commercial kits - Mwangi, Reuben; Osiany, Shebbar; Kiritu, Edward; Dobi, Paul; Ouso, Daniel; Kibet, Gilbert; Njeru, Regina; Oyola, Samuel O. (2021)
Due to worldwide shortage and the increasing cost of COVID-19 testing kits, International Livestock Research Institute (ILRI) scientists have developed in-house reconstituted testing reagents based on the known primer sequences and their targets on the SARS-COV-2 genome. The ILRI In-House reconstituted kit reduces the cost of COVID-19 RT-qPCR testing by at least 50% compared to the cheapest commercial kits available.